Association between Psychological Distress and Mental Help-Seeking Intention among Undergraduate Students; A Cross-Sectional Study - Hussain, Altaf; Wassan, Shafkatullah; Kumar, Govind; Ali, Farhan; Mahmood, Tauseef; Hussain, Imdad (Indus Journal of Bioscience Research, 2025)
Background: Psychological distress has a crucial association with mental help-seeking intentions among undergraduate. Psychological distress, including anxiety, depression, and stress, significantly affects the academic performance of undergraduate students. Depression, anxiety, and psychological distress in India, undergrads have a 63.1%, and 22.9% experienced suicidal ideation. Aim of study: To assess the association between mental distress and mental health help-seeking intention among undergraduate students. Material and Methods: The descriptive quantitative cross-sectional study design was used to assess the association between mental distress and mental health help-seeking intention among undergraduate students, the estimated sample was calculated by OpenEpi which is 279, and a nonrandom purposive sampling technique was used to collect data. There were three parts of the questionnaire used in the study. The first part was about the socio-demographic data of the participants and the second part was used to collect the mental help-seeking intention scale and the third part patient health questionnaire (PHQ-9) is used which has 10 questions if the issues plugged you in the past 2 weeks. SPSS was used for data analysis. Results: A total of 287 undergraduate students (mean age 21.42±2.75 years, 48.8% male, 51.2% female. Majority of the students, 178 (62%) fall in moderate intention level followed by greater intention, 56 (20%). A significant association was observed between psychological distress and mental help-seeking intentions. (p<0.05). While insignificant and weak negative correlation (r = -0.096) was found between scores of Psychological distress and mental help-seeking intentions (p>0.05). Conclusion: Most of the students are experiencing mental distress. These findings highlight that there is an urgent need for mental health intervention to address the issues comprehensively. Efforts should be to reduce mental distress and deal with depression. Future research should focus on a longitudinal approach to further study the mental health of undergraduates and the effectiveness of interventional strategies.